EARTHQUAKE PREDICTION: BASICS ACHIEVEMENTS, PERSPECTIVES - Kossobokov V.G. (My University, 2004)
The recent scientific advances in understanding the hierarchical nature of the lithosphere and its dynamics based on systematic monitoring and evidence of its space-energy similarity at global, regional, and local scales did result the design of reproducible intermediate-term middle-range earthquake prediction technique. The real-time experimental testing aimed at prediction of the largest earthquakes worldwide from 1992 to the present proved statistically a possibility of practical earthquake forecasting although of limited precision. In the first approximation, an accuracy of 1–5 years and 5–10 times the anticipated source dimension is achieved. Further analysis of seismic dynamics allows reducing the spatial uncertainty down to 1–3 source dimensions, although at the cost of additional failures-to-predict. Despite of limited accuracy a considerable damage could be prevented by timely knowledgeable use of the existing predictions and earthquake prediction strategies. The link of theoretical research in modeling earthquake sequences in frames of statistical physics on the one hand and instrumental and algorithm developments on the other hand help developing a new generation of earthquake prediction technique of higher accuracy.